THE EVALUATION OF CONGENITAL NEUTROPENIA PATIENTS - Nihal Karadaş (Elsevier, 2021)
Objective: Congenital neutropenia is a rare disorder. The survival and quality of lives of these patients were improved with avoidance of infections, GCSF usage and appropriate usage of antibiotics in infections.   In this study, the precautions for infections and the treatment compliance, the level of knowledge about the disease and the reasons that may affect the different behavior and compliance in our patients and caregivers were planned to be determined. Case report: Questionnaires prepared in order to determine how the social, cultural and economic conditions of the families of children with Congenital Neutropenia could affect their behavior and knowledge levels were filled in one-on-one video interviews with the caregivers. Methodology: Behaviors and attitudes of families were questioned, their level of knowledge about the disease was evaluated with a system defined over 40 points, and they were evaluated as very good (40-35), good (34-30), moderate (29-25), bad (25-20) and very bad (<19). The economic status of the families was classified by income perception. The relationship between the sociocultural economic status of the families and their knowledge and attitudes about the disease were evaluated. Results: 31 patients and 25 families were enrolled in the study. Genetic tests were performed to all patients and 70.1% homozygote HAX1 and 16.1% ELANE mutation was found. GCSF treatment was started to 96.8%. Consanguineous marriage was defined in 77.3% of families. When families were classified according to their level of knowledge about congenital neutropenia, 8% (n= 2) very good, 40% (n=10) good; 36% (n=9) moderate, 8% bad (n=2) and 8% very bad (n=2) knowledge were determined. Conclusion: Congenital neutropenia is a rare disorder. HAX 1 mutation is the most common mutation in our country. The more knowledge of patients and caregivers about the disease and general approach cause improvement in the quality of life and survival of these patients.  It is necessary to prepare tests that will enable to assess the disease knowledge level and quality of life scales developed for these patients.